Integrating Disaster Alert Kindergarten Watching into Preschool Education: Designing a Professional Disaster Mitigation Education Model to Early Children - Amelia, Lina; Hayati, Fitriah; Musdiani, Musdiani; Milfayetti, Sri; Ichsan, Ichsan (International Conference on Elementary Education, 2020)
Early childhood is a population that is considered weak and needs adults’ help when an earthquake or tsunami occurs. Early age is the golden age, which is the basis for the formation of personality and independence of children in living their lives. This research is a part of the development of disaster mitigation learning models for early childhood. The development of Disaster Alert Kindergarten Watching Learning Model in the context of providing disaster mitigation education to early children is an adoption and the development of the Town Watching Method. The town Watching Method was introduced by Prof. Dr. Ogawa Yujiro in Town Watching for Disaster Prevention Guidebook at Fuji Tokoha University in the 2010. The initial stage of the development disaster mitigation education models to early children is a stage of defining and designing the model. The definition of this model begins by analyzing the needs and characteristics of early children and the geographical environment of the targeted school, then analyzing the 2013 PAUD Curriculum to determine the indicators that can be raised in the learning model of the kindergarten watching. The analysis of these indicators results teaching materials for disaster mitigation learning models for children. This teaching materials are compiled as a benchmark for determining the age of the children that is suitable for providing disaster mitigation material that has been designed. After defining the model, the disaster mitigation learning media to early children is designed. This designing takes eight months, which is five months for designing the animated films and three months for creating the media appearance. To test the suitability and feasibility of the media to early children, a media feasibility analysis was carried out through a focus on discussion groups with 15 PAUD teachers in the TK Negeri Lamjabat of Banda Aceh. After correcting the model implementation plan according to the input of the FGD results, an initial trial of the use of the model was carried out before testing the model in a small environment. This article tells about the implementation of disaster alert kindergarten watching learning models in providing self-rescue knowledge and skills for children. The aim is to reduce disaster risk in the early childhood population